Politics and the Paul's Cross sermons, 1558-1642 - Morrissey, Mary. (Oxford : Oxford University Press, 2011)
English Reformation culture centred on 'the word preached'. Throughout this period, the most important public pulpit was Paul's Cross. This book provides a detailed history of the Paul's Cross sermons, exploring how they were delivered and the tensions between the authorities who controlled them.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Preaching -- England -- London -- History -- 16th century; Preaching -- England -- London -- History -- 17th century; Preaching -- Political aspects -- England -- London -- History -- 16th century; Preaching -- Political aspects -- England -- London -- History -- 17th century; Religion; London (England) -- Church history -- 16th century; London (England) -- Church history -- 17th century